Effects of precursors' purity on graphene quality : synthesis and thermoelectric effect - Shiau, Li Lynn (2020)
A chemical vapor deposition method has been proven to produce large scale monolayer graphene. However, it is often reported that such graphene contains a varying amount of defects. In this work, methane precursors of different purities [99.99% (4-9G), 99.90% (3-9G), and 98.90% (2-9G)] were used. It is shown that the introduction of defects occurs during graphene growth. It has been attributed to the presence of trace oxygen molecules in the gas precursors. By controlling the amount of oxygen present, one is able to tune the defect density in graphene at will. It is purported that the oxygen reacts with methane to yield methanol and formaldehyde. The latter is oxidized to formic acid. As the graphene network expands, the alcohol and formic acid are incorporated as C - O and O - C=O functional groups. In turn, the graphene experiences an overall global tensile strain due to local bond distortion induced by the electronegative oxygen containing groups. Furthermore, the presence of N2 molecules impedes the proper coalescing of carbon-containing molecules for the formation of the sp2-rich carbon network. Electrical measurement conducted suggests that a high purity precursor (4-9G) induces the least amount of defects, which confers a high Seebeck coefficient (105.1 μV/K) and a low sheet resistance (58.3 ω). In the case of a larger volume of oxygen in the precursor, electrical performance decreases generally.